Interrogation of the Structure-Activity Relationship of a Lipophilic Nitroaromatic Prodrug Series Designed for Cancer Gene Therapy Applications - Amir Ashoorzadeh; Alexandra M. Mowday; Christopher P. Guise; Shevan Silva; Matthew R. Bull; Maria R. Abbattista; Janine N. Copp; Elsie M. Williams; David F. Ackerley; Adam V. Patterson; Jeff B. Smaill (MDPI AG, 2022)
PR-104A is a dual hypoxia/nitroreductase gene therapy prodrug by virtue of its ability to undergo either one- or two-electron reduction to its cytotoxic species. It has been evaluated extensively in pre-clinical GDEPT studies, yet off-target human aldo-keto reductase AKR1C3-mediated activation has limited its use. Re-evaluation of this chemical scaffold has previously identified SN29176 as an improved hypoxia-activated prodrug analogue of PR-104A that is free from AKR1C3 activation. However, optimization of the bystander effect of SN29176 is required for use in a GDEPT setting to compensate for the non-uniform distribution of therapeutic gene transfer that is often observed with current gene therapy vectors. A lipophilic series of eight analogues were synthesized from commercially available 3,4-difluorobenzaldehyde. Calculated octanol-water partition coefficients (LogD7.4) spanned > 2 orders of magnitude. 2D anti-proliferative and 3D multicellular layer assays were performed using isogenic HCT116 cells expressing E. coli NfsA nitroreductase (NfsA_Ec) or AKR1C3 to determine enzyme activity and measure bystander effect. A variation in potency for NfsA_Ec was observed, while all prodrugs appeared AKR1C3-resistant by 2D assay. However, 3D assays indicated that increasing prodrug lipophilicity correlated with increased AKR1C3 activation and NfsA_Ec activity, suggesting that metabolite loss from the cell of origin into media during 2D monolayer assays could mask cytotoxicity. Three prodrugs were identified as bono fide AKR1C3-negative candidates whilst maintaining activity with NfsA_Ec. These were converted to their phosphate ester pre-prodrugs before being taken forward into in vivo therapeutic efficacy studies. Ultimately, 2-(5-(bis(2-bromoethyl)amino)-4-(ethylsulfonyl)-N-methyl-2-nitrobenzamido)ethyl dihydrogen phosphate possessed a significant 156% improvement in median survival in mixed NfsA_Ec/WT tumors compared to untreated controls (p = 0.005), whilst still maintaining hypoxia selectivity comparable to PR-104A.